Desenvolvimento de um sistema de apoio à decisão e operacional para a otimização dos parâmetros de corte em usinagem - Souza, Edson Melo de (2013)
The purpose of this paper is to present the development of a Decision Support and Operational System to Optimization of Cutting Parameters in Machining, being known in Portuguese as COPPISYS, for the parameter optimization of machining processes, implementing new features and improvements to systems MOS (BAPTISTA, 2004) and MOS 2 (GRIVOL, 2007). Method: The system was developed according to the Web 2.0 standards-based software development, modern computer techniques, fully object-oriented, providing fast access to data, with a friendly and intuitive interface according to standards of usability. Results: Provides sophisticated charts and reports in real time from deterministic mathematical models based on the coefficients of Taylor Tool Life Equation, using data acquired directly from the shop floor during the machining process. It also has a high degree of interactivity and flexibility to meet the different manufacturing scenarios. Conclusion: The mathematical models and calculations performed by COPPISYS provide the possibility optimization of the machining process in order to minimize costs and maximize production, aiding users in their decision making. The COPPISYS was verified by simulations and comparisons with calculations performed in previous studies with the help of spreadsheets. Moreover, it presents a module dedicated to the educational environment for the dissemination of knowledge in the area ofmachining processes and related matters.